Interview with Alena Ledeneva: To Control a Level of Informality You Need the Targeted Therapy of Informal Practices - LedenevaAlena (Journal of Economic Sociology, 2019)
In the interview, Professor Alena Ledeneva talks about her research experience, current projects, and plans. She also presents her creative guidelines for analyzing the informal economy’s worlds with the help of a context-sensitive comparative ethnographic study. Rooted in her PhD written in the mid-1990s on the contribution of blat to the functioning of the Soviet economy, the program today provides the basis for the unique empirical project, “The Global Encyclopedia of Informality,” which attracted the participation of 223 research fellows from different countries. Being publicly opened, the Encyclopedia with a base of cases describes a given informal practice’s national versions, including a list of the most recent sociological and anthropological literature for analyzing that practice. This interview demonstrates how sensitivity to ethnography’s methodological challenges allows the author to move from producing a retrospective study of the local empirical phenomenon to theorizing. The theoretical insights that Professor Ledeneva generates help to evaluate the qualities of liberal reforms, including anti-corruption policies. She shows that when the façade of formal institutions is invisibly based on rigidity and double standards, informal practices contribute to both creating and destroying of social systems. Until the conflict between rules issued from the top and reaction from the bottom is taken into account during social and political transformations, the minimizing of corruption will be difficult. In the interview, Professor Ledeneva shares her research experience and demonstrates how she struggled for validity of the conclusions in her qualitative research through comparisons of empirical evidences from different sources. She also discusses the challenges from her in-depth interviews implying discussions of sensitive topics and how they could be overcome. Particularly, Alena refers to her approach to ethnography of informal economy as a “method of slow cooking.” This interview, however, may produce impressions that Alena’s “field kitchen” tends to be molecular.